CAUSES AND SYMPTOMS OF HIP DYSPLASIA - Mansurova Gulnoza Muyinjanovna; Xamroyeva Shoira Ergashovna (Web of Journals Publishing, 2025)
The causes and mechanisms of development of hip dysplasia are complex and not fully understood. There is a theory that dysplasia is caused by inflammation of the hip joint capsule (synovitis). According to the paralytic theory, congenital hip dysplasia is caused by poliomyelitis in the womb. Supporters of acute trauma believe that trauma during childbirth causes hip dysplasia.
Keywords: Genetic condition, cartilage, hip pain, hip dislocation, Hip labral tears.